2009
DOI: 10.1111/j.1365-2249.2008.03832.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein levels of CC chemokine ligand (CCL)15, CCL16 and macrophage stimulating protein in patients with sarcoidosis

Abstract: SummaryThe objective of this study was to assess protein levels for candidate cytokines, chemokines, growth factors, matrix metalloproteinases and their inhibitors in bronchoalveolar lavage fluid (BALF) in patients with polar forms of pulmonary sarcoidosis, i.e. Löfgren's syndrome (LS) and more advanced chest X-ray (CXR) stage III disease. Twenty-four inflammatory molecules were analysed in unconcentrated BALF samples from 10 sarcoidosis patients with CXR stage III and 10 patients with LS by semiquantitative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 31 publications
(36 reference statements)
4
26
0
Order By: Relevance
“…The increased concentrations of CXCR3 ligands in BAL fluid from patients with sarcoidosis have been reported by a number of studies 4,7-9 ; however, their results were inconsistent. For instance, Busuttil et al 4 reported elevated CXCL9 levels but did not confirm elevated CXCL10 levels in BAL fluid in this patient group, while Arakelyan et al 17 did not find significant differences in the BAL fluid levels of CXCL9 and CXCL10 between the sarcoidosis and control groups, which is in line with our study. These discrepancies may be explained by the polymorphic and highly variable clinical course of the disease and different patient selection criteria.…”
Section: Abbreviations: Ns -Nonsignificantsupporting
confidence: 87%
“…The increased concentrations of CXCR3 ligands in BAL fluid from patients with sarcoidosis have been reported by a number of studies 4,7-9 ; however, their results were inconsistent. For instance, Busuttil et al 4 reported elevated CXCL9 levels but did not confirm elevated CXCL10 levels in BAL fluid in this patient group, while Arakelyan et al 17 did not find significant differences in the BAL fluid levels of CXCL9 and CXCL10 between the sarcoidosis and control groups, which is in line with our study. These discrepancies may be explained by the polymorphic and highly variable clinical course of the disease and different patient selection criteria.…”
Section: Abbreviations: Ns -Nonsignificantsupporting
confidence: 87%
“…Of the studied chemokine receptors, we observed a strong correlation between T-bet and CXCR6, a receptor co-expressed on CXCR3 T-cells in sarcoidosis [4]. Furthermore, a strong correlation was observed between T-bet and CCL5 and CXCL10, two chemokines that play an important role in the recruitment of T-cells to the sarcoid lungs [4,[15][16][17]19]. Additionally, we observed a strong association between T-bet and IL-2R/IL-15Rb (CD122) in our sarcoidosis patients; this association has been already reported in animal cell cultures [5,7].…”
Section: Discussionmentioning
confidence: 71%
“…Determination of cell-associated T-bet protein by immunocytochemistry T-bet protein was detected on the acetone-chloroform fixed cytocentrifuge preparations of BAL cells using the streptavidin-biotin/horseradish peroxidase method using an anti-T-bet antibody (clone 525803, dilution 1:50; R&D Systems Inc.) and a negative control mouse IgG1 (clone DAK-GO1, dilution 1:50; Dako) as described previously [16]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations